Exploring the Changing Nature of Work and Lifelong Learning: Preliminary Findings of a Canadian National Survey - David Livingstone (Adult Education Research Conference, 2004)
Preliminary findings from a large Canadian survey are used to estimate the current patterns of adult education course participation and informal learning as well as patterns of paid and unpaid work. Recent trends and relations between adult learning and work are assessed. Contending theories of learning and work are also discussed.